(untitled) (The Research of Medical Science Review, 2024)
Aquatic species and ecosystem health are significantly impacted by marine plastic waste, which has become a global environmental emergency. This analysis highlights the wide distribution of plastic pollution from coastal seas to the deep sea by examining its sources, kinds, and transport mechanisms. Physical harm from eating and entanglement, toxicological consequences from chemical leaching and pollutant absorption, and disturbances in behavior and reproduction are some of the main effects on marine creatures. Plastic waste changes habitats upends food webs, and affects the dynamics of microbial communities by forming plastispheres at the ecosystem level. The efficacy and limitations of current mitigation strategies, including source reduction, cleanup campaigns, and legislative actions, are assessed. The assessment also points out areas that require more investigation, especially to comprehend the long-term ecological effects and develop sustainable substitutes for traditional plastics. This study emphasizes how urgently international cooperation is required to combat marine plastic pollution to protect biodiversity and preserve ecosystem integrity.